2017
DOI: 10.1021/acsnano.7b04177
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes as Thermally Induced Water Pumps

Abstract: Thermal Brownian motors (TBMs) are nanoscale machines that exploit thermal fluctuations to provide useful work. We introduce a TBM-based nanopump which enables continuous water flow through a carbon nanotube (CNT) by imposing an axial thermal gradient along its surface. We impose spatial asymmetry along the CNT by immobilizing certain points on its surface. We study the performance of this molecular motor using molecular dynamics (MD) simulations. From the MD trajectories, we compute the net water flow and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 50 publications
2
46
0
2
Order By: Relevance
“…In the NVE ensemble, no external thermostat was applied. Therefore, our directional motion is spontaneously achieved by the stiffness gradient without applying external driving forces, which is different from the motion realized by an external thermal gradient 13,15 and stiffness gradient induced by a thermal gradient. 42 It is worth noting that although the motion of water molecules inside the CNT is a spontaneous process without resorting to any active driving source, a certain amount of energy is still required to push water molecules entering the CNT, which is the general behaviour for any type of water channel.…”
Section: Mechanism Of Directional Water Transportation Induced By Thementioning
confidence: 89%
See 2 more Smart Citations
“…In the NVE ensemble, no external thermostat was applied. Therefore, our directional motion is spontaneously achieved by the stiffness gradient without applying external driving forces, which is different from the motion realized by an external thermal gradient 13,15 and stiffness gradient induced by a thermal gradient. 42 It is worth noting that although the motion of water molecules inside the CNT is a spontaneous process without resorting to any active driving source, a certain amount of energy is still required to push water molecules entering the CNT, which is the general behaviour for any type of water channel.…”
Section: Mechanism Of Directional Water Transportation Induced By Thementioning
confidence: 89%
“…Since the demonstration of the excellent behavior of carbon nanotubes (CNTs) as a water transportation channel by Hummer et al 2 in 2001, many nanoscale water channels based on CNTs have been reported, and important progress has been made in understanding their transport behaviors. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For example, for nanoscale channels based on CNTs, the structure of nanotubes 16 and dopant atoms 17 may greatly affect the water permeation rate. In multi-walled carbon nanotubes (MWCNTs), the nanotube type and layer number may also exert strong inuence on the water transport behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the effect of externally applied electric fields in capillary filling of water in hydrophilic silica nanopores, we conduct a series of all-atom MD simulations using FAST-TUBE, a molecular dynamics simulation package which has widely been used to investigate fundamental fluid dynamics under nanoconfinement. 29,42,45,[63][64][65] Water molecules are described using the simple point charge SPC/E model 66 and the silica atoms by the TTAMm model developed by Guissani and Guillot 67 which is a modification of the original TTAM model. 68 Water-silica interactions are described using Coulomb and Buckingham potentials calibrated in our previous study 69 wherein the experimental value of the water contact angle reported by Thamdrup et al 70 in studies of capillary filling is used as criterion to calibrate the potential parameters.…”
Section: Methodsmentioning
confidence: 99%
“…At first, the thermophoric phenomena along a carbon nanotube [ 1 5 ] or a graphene ribbon [ 6 10 ] have been extensively investigated. Thermal fluctuations are confirmed to enable continuous water flow through a carbon nanotube (CNT) by imposing an axial thermal gradient along its surface [ 11 13 ]. Nonequilibrium molecular dynamics simulations are done to explore the feasibility of utilizing a thermal gradient on a large graphene substrate to control the motion of a small graphene nanoflake [ 6 ].…”
Section: Introductionmentioning
confidence: 99%